The duration of using denture againts plaque formation of denture base - Diana Setya Ningsih; Liana Rahmayani; Zaki Mubarak (Dentistry Faculty, 2020)
The assessment of denture plaque can provide valuable information regarding the status of denture hygiene. Denture hygiene is strongly influenced by the patient's socioeconomic condition and the duration of denture use. The commonly used material is the heat cure acrylic resin, which can naturally increase the surface roughness if used for a long time. To determine the differences in the formation of plaque in the denture intaglio in denture use duration. As many as 14 (fourteen) respondents as research subjects used the heat-cured acrylic resin denture and came to one of the Primary clinics in Banda Aceh between April-May 2020 (During the COVID-19 Pandemic). These subjects were divided into three groups, namely 1 year, 1-3 years, and three years. In this study, the assessment of denture plaque score was conducted by the visual plaque assessment method. The colored area was the intaglio denture area, which was left for 5 minutes. The images obtained were converted into the Tarbet index (Score 1-4). The study showed that each group's denture plaque scores had different denture plaque scores. The highest denture plaque scores were found in dentures used 1-3 years. Compared to 1 year and 3 years of use. The duration of use can affect the formation of denture plaque